2014
DOI: 10.1007/s11157-014-9342-6
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive overview of bacteria and fungi used for pentachlorophenol biodegradation

Abstract: Pentachlorophenol (PCP) is an extremely dangerous worldwide pollutant due to its high toxicity towards all organisms. It has been introduced into the environment mainly as a wood preservative, biocides and from the bleaching of paper or tissues. The use of PCP indiscriminate has led to the contamination of water and soil systems. Many countries have specific regulations, guidelines or procedures for the management and disposal of PCP but the most common methods are: adsorption with activate carbons, incinerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 117 publications
1
38
0
Order By: Relevance
“…Strains belonging to the species Fusarium oxysporum , Penicillium brevicompactum , P. glabrum , P. janczewskii , P. radiatolobatum , P. restrictum , P. murcianum , P. sizovae , P. vagum and P. vanoranjei were able to degrade ≥ 50% of the 56 μM of PCP in media (Table ). These data are consistent with the capacity of penicillia to utilize a wide variety of simple aromatic compounds (Field and Sierra‐Alvarez, ; Leitão, ; Bosso and Cristinzio, ). Soils are composed of interconnected but distinctive microenvironments holding specific microbial colonizers and concentration/diversity of pollutants (Harms et al ., ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Strains belonging to the species Fusarium oxysporum , Penicillium brevicompactum , P. glabrum , P. janczewskii , P. radiatolobatum , P. restrictum , P. murcianum , P. sizovae , P. vagum and P. vanoranjei were able to degrade ≥ 50% of the 56 μM of PCP in media (Table ). These data are consistent with the capacity of penicillia to utilize a wide variety of simple aromatic compounds (Field and Sierra‐Alvarez, ; Leitão, ; Bosso and Cristinzio, ). Soils are composed of interconnected but distinctive microenvironments holding specific microbial colonizers and concentration/diversity of pollutants (Harms et al ., ).…”
Section: Discussionsupporting
confidence: 85%
“…Numerous studies have demonstrated an increasing abundance and diversity of fungi in chronically stressed and polluted soils (Ramsey et al ., ; Lladó et al ., ). Consequently, PCP degradation by fungi has been widely studied, but only a limited number of degradation pathways have been completely, or even partially, elucidated by analysing metabolites and proteins in pure cultures (Reddy and Gold, ; Gadd, ; Field and Sierra‐Alvarez, ; Carvalho et al ., ; Bosso and Cristinzio, ). Data available on bacterial communities indicate broad capacity to undertake successive reductive dechlorination reactions yielding non‐chlorinated or chlorinated phenol derivatives, usually highly toxic and recalcitrant (Field and Sierra‐Alvarez, ; Zhang et al ., ; Bosso and Cristinzio, ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, little is actually known about the metabolic pathway of PCP in white rot fungi. Bosso and Cristinzio [20] showed also that the main reaction of PCP degradation in A. discolor was methylation with the formation of PCA, and the second reaction was hydroxylation in the form of TCHQ, which is then methylated to generate TCDB, followed by successive reactions to form dechlorination products. A complete dechlorination pathway of PCP in P. chrysosporium different from that in our study has been reported by Reddy and Gold [21], who found that PCP is first oxidized by LiP or MnP to tetrachlorobenzoquinone, which apparently is further degraded by two parallel pathways with several cross-pathway steps.…”
Section: Degradation Pathway Of Pcp By P Acanthocystismentioning
confidence: 97%
“…When PCP enters the soil, it undergoes a slow natural dissipation , and the biodegradation of PCP has been proposed to be the most important PCP removal process in soils (Kim et al 2004;Yoshida et al 2007;Field and SierraAlvarez 2008;Juwarkar et al 2010;Bosso and Cristinzio Responsible editor: Robert Duran Electronic supplementary material The online version of this article (doi:10.1007/s11356-016-7562-8) contains supplementary material, which is available to authorized users. 2014).…”
Section: Introductionmentioning
confidence: 99%